Behaviour of concrete confined by circular and elliptical hoops inder axial loads - Tan, Teng Hooi. (2009)
The thesis is about the investigation of the behaviour of concrete confined by lateral reinforcement. Experimental program for the testing of the confined concrete using circular spirals and elliptical hoops is described. Those specimens with circular spirals were tested under monotonic and cyclic axial loads whereas those with elliptical hoops were tested under monotonic axial load only.